Tpr, a large coiled coil protein whose amino terminus is involved in activation of oncogenic kinases, is localized to the cytoplasmic surface of the nuclear pore complex (The Rockefeller University Press, 1994)
From a panel of monoclonal antibodies raised against fractions of rat liver nuclear envelopes (NEs), we have identified an antibody, RL30, which reacts with novel nuclear pore complex (NPC) antigens that are not O-glycosylated. By immunofluorescence staining of cultured cells, RL30 reacts exclusively with the NE in a punctate pattern that largely coincides with that of identified NPC proteins. RL30 labels only the cytoplasmic surface of the NPC in immunogold electron microscopy, predominantly in peripheral regions nearby the cytoplasmic ring. In immunoblots of isolated rat liver NEs and cultured rat cells, RL30 recognizes a 265-kD band, as well as a series of 175-265-kD bands in rat liver NEs that are likely to be proteolytic products of p265. Sequencing of peptides from the 175- and 265-kD RL30 antigens of rat liver revealed that they are both closely related to human Tpr, a protein whose amino-terminal 150-250 amino acids appear in oncogenic fusions with the kinase domains of the met, trk, and raf protooncogenes. We found that in vitro translation of human Tpr mRNA yields a major 265-kD band. Considered together, these data indicate that the 265-kD RL30 antigen in the NPC is the rat homologue of Tpr. Interestingly, Tpr contains an exceptionally long predicted coiled coil domain (approximately 1600 amino acids). The localization and predicted structure of Tpr suggest that it is a component of the cytoplasmic fibrils of the NPC implicated in nuclear protein import. Immunofluorescence microscopy shows that during NPC reassembly at the end of mitosis, Tpr becomes concentrated at the NE significantly later than O-linked glycoproteins, including p62. This indicates that reassembly of the NPC after mitosis is a stepwise process, and that the Tpr-containing peripheral structures are assembled later than p62.